1993
DOI: 10.1111/j.1365-2621.1993.tb06191.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Affects Astringency Removal and Recurrence in Persimmon

Abstract: Astringency was removed from 'Triumph' persimmons by immersion in water at 40°C for 5 hr or 6O"C, for 1 hr. Similar treatments at 20" and 8O"C, had no effect on astringency reduction. Subsequent application of 80% CO2 for 48 hr was effective for 20"C-treated fruit but not for 80YXreated fruit, which became nonastringent only after exposure to acetaldehyde. Extending the 60°C treatment beyond 2 hr resulted in recurrence of astringency, which was not reduced by subsequent COz treatment. Astringency also recurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 9 publications
0
19
0
2
Order By: Relevance
“…On the other hand, as pinpointed for the origin of astringency perception in the oral cavity, tannins bind readily with proteins to form quite indigestible complexes and can therefore be considered as antinutritional compounds in herbivores (Salunkhe, Chavan, & Kadam, 1989). Moreover, as suggested by Ben-Arie and Sonego (1993), tannins resolubilised during human digestion can be involved in the occurrence of persimmon bezoars, hard masses occasionally found in the human stomach or intestine (Seung et al, 2007), with a higher frequency in patients subjected to gastric surgery (Moriel et al, 1983). In this regard, Ben-Arie and Sonego (1993) hypothesized that the formation of persimmon bezoars is caused by resolubilization of insoluble tannins by the high acidity occurring in the human stomach during digestion and successive re-coagulation of solubilised tannins with proteins and/or other macromolecules present in the stomach.…”
Section: Soluble Polyphenol Contentmentioning
confidence: 88%
See 1 more Smart Citation
“…On the other hand, as pinpointed for the origin of astringency perception in the oral cavity, tannins bind readily with proteins to form quite indigestible complexes and can therefore be considered as antinutritional compounds in herbivores (Salunkhe, Chavan, & Kadam, 1989). Moreover, as suggested by Ben-Arie and Sonego (1993), tannins resolubilised during human digestion can be involved in the occurrence of persimmon bezoars, hard masses occasionally found in the human stomach or intestine (Seung et al, 2007), with a higher frequency in patients subjected to gastric surgery (Moriel et al, 1983). In this regard, Ben-Arie and Sonego (1993) hypothesized that the formation of persimmon bezoars is caused by resolubilization of insoluble tannins by the high acidity occurring in the human stomach during digestion and successive re-coagulation of solubilised tannins with proteins and/or other macromolecules present in the stomach.…”
Section: Soluble Polyphenol Contentmentioning
confidence: 88%
“…Moreover, as suggested by Ben-Arie and Sonego (1993), tannins resolubilised during human digestion can be involved in the occurrence of persimmon bezoars, hard masses occasionally found in the human stomach or intestine (Seung et al, 2007), with a higher frequency in patients subjected to gastric surgery (Moriel et al, 1983). In this regard, Ben-Arie and Sonego (1993) hypothesized that the formation of persimmon bezoars is caused by resolubilization of insoluble tannins by the high acidity occurring in the human stomach during digestion and successive re-coagulation of solubilised tannins with proteins and/or other macromolecules present in the stomach. The re-coagulating capacity of resolubilized tannins has been experimentally highlighted by Seung et al (2007) on a patient with an intestinal persimmon bezoar resulting from the solubilisation of a previously diagnosed gastric bezoar.…”
Section: Soluble Polyphenol Contentmentioning
confidence: 88%
“…Anaerobic conditions stimulate production of acetaldehyde and ethanol by the fruits; the mechanism involves soluble tannins in the fresh fruit becoming insoluble upon condensation or polymerization with acetaldehyde (Pesis et al, 1988;Taira & Ono, 1997). A method commonly used is to enclose the fruit for 1-2 days in a CO 2 -enriched atmosphere (>80% CO 2 ) (Ben-Arie & Sonego, 1993;Pesis et al, 1988). Pesis et al (1988) indicated, astringency was removed more rapidly under CO 2 than under vacuum and the de-astringency process under N 2 was the slowest.…”
Section: Introductionmentioning
confidence: 99%
“…Most research relating to persimmon has been on storage conditions (cold and controlled atmosphere storage) after harvest, and has been carried out to determine astringency, color and firmness (Ben-Arie & Sonego, 1993;Kitagawa & Glucina, 1984;Pesis, Levi, & BenArie, 1988). Furthermore in some studies, invertase and pectin esterase were isolated and their characteristics were investigated (Alonso, Howel, & Canet, 1997;Iwatsobu, Takahashi, Nakagawa, Ogura, & Sato, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation